2011
DOI: 10.1021/cg2003222
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation and Analysis of Single-Domain YBCO Bulk Superconductor by TSIG Process

Abstract: The growth process of single domain YBCO bulk superconductor by top-seeded infiltration and growth technique has been observed in real time by an in situ high temperature video camera. The initial epitaxial growth temperature from the NdBCO seed and growth rate of a single domain YBCO bulk were obtained by measuring the growth distance between the seed and the growing interface at different times. It was found that the initial epitaxial growth temperature of YBCO crystal is about 1008 °C; the average growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…It has been found that a reduction in the size of RE 2 BaCuO 5 '(RE)-211' secondary-phase particles embedded within the superconducting (RE)Ba 2 Cu 3 O 7−y '(RE)-123'-phase matrix that occur naturally as a result of the melt growth process improves the critical current density of (RE)BCO [10][11][12]. The concentration of Y-211 particles in YBCO is known to vary considerably from the region close to the seed crystal to the edge/bottom of the sample [13]. This is an unavoidable effect, which occurs due to particle pushing effects associated with the YBa 2 Cu 3 O 7−x (Y-123) growth front.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that a reduction in the size of RE 2 BaCuO 5 '(RE)-211' secondary-phase particles embedded within the superconducting (RE)Ba 2 Cu 3 O 7−y '(RE)-123'-phase matrix that occur naturally as a result of the melt growth process improves the critical current density of (RE)BCO [10][11][12]. The concentration of Y-211 particles in YBCO is known to vary considerably from the region close to the seed crystal to the edge/bottom of the sample [13]. This is an unavoidable effect, which occurs due to particle pushing effects associated with the YBa 2 Cu 3 O 7−x (Y-123) growth front.…”
Section: Introductionmentioning
confidence: 99%
“…A seed crystal (whose melting temperature is above the T p of the seeded bulk, but with similar crystal lattice parameters and having phase stability with the melt) is employed for seeding and subsequent growth of YBCO into a single grain. The growth rate of the Y-123 phase is of the order of 0.2-0.4 mm/h [12,13], which limits practically the ultimate size of the final single grain. Additionally, it has been reported previously that large samples exhibit increasing crystallographic misorientation of the Y-123 phase with increasing distance from the seed [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, no matter how the MG or the IG technique is used, the sample reaches a partial melting state composed of RE-211 solid phase and Ba–Cu–O liquid phase at high temperatures, and the seed crystal promotes the epitaxial, heterogeneous nucleation of RE-123 in the melt and subsequently induces the directional growth of the RE-123 individual grain to a large scale, and finally to the whole bulk size . Finally clear, 4-fold a -growth sectors ( a -GS) are exhibited on the top surface of the as-grown sample, which is known as the typical morphology feature of top-seeded RE-123 single grains and usually named “X-type” pattern. Actually, in the directions of the a axis ( 100 ) and the c axis ( 001 ), the seed crystal initiates epitaxial growth of five sectors, including four a -GS and one c -growth sector ( c -GS).…”
Section: Introductionmentioning
confidence: 99%
“…It resulted hence in the avoidance of the oxygen bubbles entrapment during the crystal growth and, subsequently, in pore-free microstructure. The crystal growth was oriented by a commercial 2 × 2 mm 2 seed, NdBCO thin layer deposited on MgO substrate (Theva Gmbh films), , placed on the upper surface of the precursor prior to TSMG processing.…”
mentioning
confidence: 99%